2005
DOI: 10.1080/08035320510043655
|View full text |Cite
|
Sign up to set email alerts
|

Novel approaches to the nutritional management of the allergic infant

Abstract: The increased prevalence of atopic diseases, i.e. atopic eczema, allergic rhinitis and asthma, has been described as the epidemic of the 21st century in Western societies. New approaches in the fight against allergic diseases are clearly called for, the target being the persistence of the allergic responder pattern beyond infancy. The advantage afforded by elimination diets lies in the silencing of specific allergic inflammation induced by an offending food. Novel nutritional approaches, beyond the treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Similarly, another study suggested that treatment with Lactobacillus GG may alleviate atopic eczema/dermatitis syndrome symptoms in IgE-sensitized infants but not in non-IgE-sensitized infants , while a 4-week treatment with Lactobacillus GG alleviated intestinal inflammation in infants with atopic eczema/ dermatitis syndrome and milk allergy (Viljanen, Kuitunen, et al, 2005). The mechanisms of the protective effects of probiotics on allergic reactions are not entirely known; although the reinforcement of the different lines of gut defence including immune exclusion, immune elimination and immune regulation has been suggested (Isolauri, Ouwehand, & Laitinen, 2005).…”
Section: Treatment and Prevention Of Allergymentioning
confidence: 96%
“…Similarly, another study suggested that treatment with Lactobacillus GG may alleviate atopic eczema/dermatitis syndrome symptoms in IgE-sensitized infants but not in non-IgE-sensitized infants , while a 4-week treatment with Lactobacillus GG alleviated intestinal inflammation in infants with atopic eczema/ dermatitis syndrome and milk allergy (Viljanen, Kuitunen, et al, 2005). The mechanisms of the protective effects of probiotics on allergic reactions are not entirely known; although the reinforcement of the different lines of gut defence including immune exclusion, immune elimination and immune regulation has been suggested (Isolauri, Ouwehand, & Laitinen, 2005).…”
Section: Treatment and Prevention Of Allergymentioning
confidence: 96%
“…The mechanism of the preventative impact of probiotics on allergic reactions is not well known. However, the reinforcement of the different mechanisms of gut defence, including immune exclusion, immune elimination, and immune regulation has been suggested (Isolauri et al 2005). Early consumption of probiotic preparations containing Lactobacillus GG may reduce prevalence of atopic eczema later in life (Gueimonde et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…V Fully established allergic disease: consolidation of the immune responder type; control of allergic inflammation. Figure modified from Isolauri [73].…”
Section: Resultsmentioning
confidence: 97%
“…The treatment of food allergy should therefore counteract the mechanisms that initiate and perpetuate intestinal inflammation and promote mechanisms that terminate immunoinflammatory responses ( Fig. 1) [73]. All these aspects of the gut barrier function are potential targets for probiotic intervention.…”
Section: Resultsmentioning
confidence: 99%